Technology and innovation for social change - Majumdar, Satyajit; Guha, Samapti; Marakkath, Nadiya (Springer India Imprint: Springer, 2015)
Tension exists between technologists and social thinkers because of the impact technology and innovation have on social values and norms, which is often viewed as damaging to the cultural fabric of a nation or society. Since the global business environment is the context in which implementation of technology and innovation takes place, it is widely accepted as the major reason for such conflicts. In this backdrop, this edited book integrates independent research from across the globe. It deals with the nature and significance of technology, innovation and social change as well as the relationships between them, and discusses the significance of social entrepreneurship from social innovation and technology perspectives. Research areas covered are related to the development and deployment of technology, innovation and knowledge in social change, capabilities of institutions, models, role of government and corporate social responsibility and community involvement. Multiple aspects of social change are discussed in the context of India, Mexico, Thailand, Cambodia, Laos, Vietnam, Ethiopia, Nigeria and other African countries. But society does not silently accept technologically enforced changes; sometimes technology is seen as an enemy of inclusive growth and for many, economic development is an anti-thesis of social change. Selected case studies on sector-specific technologies, such as the use of genetically modified seeds in agriculture, which has impacted the market and society, are critically analyzed to develop insights into the adoption of technology and its impact. At the same time it examines policy related issues, without any bias in favor of, or against, a specific technology.